Bottom-up and top-down effects in a pre-dispersal seed predation system: are non-predated seeds damaged? - De Menezes, Luciana C. C. R. [UNESP]; Klein, Jeferson [UNESP]; Kestring, Debora [UNESP]; Rossi, Marcelo N. (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
Seed predators that severely affect seed germination rates are well known for many plant species. Here, we hypothesised that due to differences in resource allocation within fruits, seed predation can negatively affect non-predated seeds in infested fruits when predation occurs during fruit maturation (a 'top-down' effect). We addressed this question using a system of bruchid beetles on Mimosa trees and we also investigated whether seed quality (nitrogen concentration) affects beetle body mass, which would have implications for adult fitness ('bottom-up' effect). To assess spatial variation, bottom-up and top-down effects were investigated in two plant populations. Nitrogen concentration was significantly higher in seeds from non-infested fruits than from infested fruits. This supports the hypothesis that resource allocation may differ between seeds from infested and non-infested fruits. Germination experiments showed that seeds from non-infested fruits germinated better than non-predated seeds from infested fruits. It was also confirmed that seed quality affected bruchid body mass. There was also evidence that more resources were taken from well-developed seeds. These results showed that seed predation can damage non-predated seeds. (C) 2009 Gesellschaft fur Okologie. Published by Elsevier Gmbh. All rights reserved.
Keywords: Acanthoscelides schrankiae; Bruchidae; Insect-plant interaction; Mimosa bimucronata; Seed germination; Seed quality